2004
DOI: 10.1186/gb-2004-5-7-229
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We assess five years of usage of the major genome-wide collections of mutants from Saccharomyces cerevisiae: single deletion mutants, double mutants conferring 'synthetic' lethality and the 'TRIPLES' collection of mutants obtained by random transposon insertion. Over 100 experimental conditions have been tested and more than 5,000 novel phenotypic traits have been assigned to yeast genes using these collections. The electronic version of this article is the complete one and can be found online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…Since their first publication in 1999, the barcoded budding yeast deletion collections have markedly accelerated the pace of discovery in diverse fields that can take advantage of a yeast model [3,63]. We expect that the method we report in this paper will help the barcoded fission yeast deletion collections fulfill their potential and make far-reaching contributions in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…Since their first publication in 1999, the barcoded budding yeast deletion collections have markedly accelerated the pace of discovery in diverse fields that can take advantage of a yeast model [3,63]. We expect that the method we report in this paper will help the barcoded fission yeast deletion collections fulfill their potential and make far-reaching contributions in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…Each knockout strain is marked by two unique 20-bp barcodes, allowing quantitative and qualitative identification [32]. …”
Section: Functional Genomics In Yeastmentioning
confidence: 99%
“…These genome-scale genetic interactions studies were facilitated by the availability of large collections of deletion strains and the development of automated platforms to analyze the phenotypes of double mutants (Scherens and Goffeau, 2004). Since the first large-scale genetic interaction study in yeast identified 4000 genetic interactions among 1000 genes when analyzing synthetic lethality in double deletion mutants (Tong et al, 2004), the field advanced considerably.…”
Section: Introductionmentioning
confidence: 99%